Impacts of changing climate and land use on vegetation dynamics in a Mediterranean ecosystem: insights from paleoecology and dynamic modeling - Henne, Paul D.; Elkin, Ché; Colombaroli, Daniele; Samartin, Stéphanie; Bugmann, Harald; Heiri, Oliver; Tinner, Willy (Landscape Ecology, 2012)
Forests near the Mediterranean coast have been shaped by millennia of human disturbance. Consequently, ecological studies relying on modern observations or historical records may have difﬁculty assessing natural vegetation dynamics under current and future climate. We combined a sedimentary pollen record from Lago di Massacciucoli, Tuscany, Italy with simulations from the LANDCLIM dynamic vegetation model to determine what vegetation preceded intense human disturbance, how past changes in vegetation relate to ﬁre and browsing, and the potential of an extinct vegetation type under present climate. We simulated vegetation dynamics near Lago di Massaciucoli for the last 7,000 years using a local chironomid-inferred temperature reconstruction with combinations of three ﬁre regimes (small infrequent, large infrequent, small frequent) and three browsing intensities (no browsing, light browsing, and moderate browsing), and compared model output to pollen data. Simulations with low disturbance support polleninferred evidence for a mixed forest dominated by Quercus ilex (a Mediterranean species) and Abies alba (a montane species). Whereas pollen data record the collapse of A. alba after 6000 cal yr BP, simulated populations expanded with declining summer temperatures during the late Holocene. Simulations with increased ﬁre and browsing are consistent with evidence for expansion by deciduous species after A. alba collapsed. According to our combined paleoenvironmental and modeling evidence, mixed Q. ilex and A. alba forests remain possible with current climate and limited disturbance, and provide a viable management objective for ecosystems near the Mediterranean coast and in regions that are expected to experience a mediterranean-type climate in the future.
Keywords: Abies alba; Chironomids; Fire ecology; Holocene; Italy; Landscape model; mediterranean forest; Neolithic; pollen; Quercus ilex

Response of broadleaved evergreen Mediterranean forest vegetation to fire disturbance during the Holocene: insights from the peri-Adriatic region - Colombaroli, Daniele; Tinner, Willy; van Leeuwen, Jacqueline; Noti, Roland; Vescovi, Elisa; Vannière, Boris; Magny, Michel; Schmidt, Roland; Bugmann, Harald (Journal of Biogeography, 2009)
Aim To test whether fire contributed to the expansion and compositional change of evergreen forests in the Mediterranean region during the Holocene. Location The peri-Adriatic region, encompassing the Italian peninsula, Sicily and the western and southern Balkans between latitudes 46° and 37° N. Methods New high-resolution pollen and microscopic charcoal data from Lago dell’Accesa (Tuscany, Italy) were used to estimate the response of the evergreen oak, Quercus ilex L., to fire during its expansion phase at 8500 cal. yr bp. The data were compared with the pollen and charcoal series from other Mediterranean sites (Lago di Massaciuccoli in Tuscany, Malo Jezero in Croatia, Biviere di Gela in Sicily) and analysed using numerical techniques (redundancy analysis, detrended canonical correspondence analysis) to identify long-term fire–vegetation linkages and the degree of compositional change. Results Microscopic charcoal and pollen of evergreen oaks were negatively correlated during the period of quasi-natural fire regime (Mesolithic, 10,000–8000 cal. yr bp). In addition, there was no such positive correlation during periods when the fire regime was potentially more influenced by people (Neolithic–Bronze Age, 8000–3000 cal. yr bp). Compared with inland sites, coastal sites that are currently located at a distinct ecotone showed more compositional change. Main conclusions The analyses suggest that climatic change, without an additional effect of fire regimes, favoured the expansion and compositional change of evergreen forests across the peri-Adriatic region. Strikingly different patterns occurred along a north–south gradient. In the north (Tuscany and Croatia, meso-Mediterranean belt), Q. ilex replaced deciduous forests when conditions became drier; in the south (Sicily, thermo-Mediterranean belt) the species replaced maquis or steppe vegetation when climatic conditions became moister. We conclude that the projected increase in fire activity may lead to the loss of most of the remaining relict forests of Q. ilex in southern Europe.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Compositional change; cross-correlations; Fire history; Mediterranean vegetation; microscopic charcoal analysis; Pollen analysis; Quercus ilex; redundancy analysis; species diversity

Response of broadleaved evergreen Mediterranean forest vegetation to fire disturbance during the Holocene: insights from the peri-Adriatic region (Journal of Biogeography, 2009)
Aim To test whether fire contributed to the expansion and compositional change of evergreen forests in the Mediterranean region during the Holocene. Location The peri-Adriatic region, encompassing the Italian peninsula, Sicily and the western and southern Balkans between latitudes 46° and 37° N. Methods New high-resolution pollen and microscopic charcoal data from Lago dell’Accesa (Tuscany, Italy) were used to estimate the response of the evergreen oak, Quercus ilex L., to fire during its expansion phase at 8500 cal. yr bp. The data were compared with the pollen and charcoal series from other Mediterranean sites (Lago di Massaciuccoli in Tuscany, Malo Jezero in Croatia, Biviere di Gela in Sicily) and analysed using numerical techniques (redundancy analysis, detrended canonical correspondence analysis) to identify long-term fire–vegetation linkages and the degree of compositional change. Results Microscopic charcoal and pollen of evergreen oaks were negatively correlated during the period of quasi-natural fire regime (Mesolithic, 10,000–8000 cal. yr bp). In addition, there was no such positive correlation during periods when the fire regime was potentially more influenced by people (Neolithic–Bronze Age, 8000–3000 cal. yr bp). Compared with inland sites, coastal sites that are currently located at a distinct ecotone showed more compositional change. Main conclusions The analyses suggest that climatic change, without an additional effect of fire regimes, favoured the expansion and compositional change of evergreen forests across the peri-Adriatic region. Strikingly different patterns occurred along a north–south gradient. In the north (Tuscany and Croatia, meso-Mediterranean belt), Q. ilex replaced deciduous forests when conditions became drier; in the south (Sicily, thermo-Mediterranean belt) the species replaced maquis or steppe vegetation when climatic conditions became moister. We conclude that the projected increase in fire activity may lead to the loss of most of the remaining relict forests of Q. ilex in southern Europe.